The Impact of ESG Scores on Sustainable Banking Performance: Evidence from Islamic and Conventional Banks in Indonesia - Estu Widarwati; Gelia Rahma; Robit Kisey Gardenas; E Wityasminigsih; Ardhia Indrani Davina (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) Score on Sustainable Banking Performance in banks listed on the Indonesia Stock Exchange during the 2023–2025 period. As ESG has become an important pillar of sustainable finance, understanding its impact on banking performance is increasingly relevant, particularly from the perspective of long-term value creation and ethical governance. The study is grounded in Financial Management Theory and supported by Stakeholder Theory and Signaling Theory to explain the relationship between ESG implementation and sustainable banking performance. A quantitative approach was employed using secondary data from annual reports and ESG disclosures of 36 listed banks, resulting in 108 firm-year observations selected through purposive sampling. Sustainable Banking Performance was proxied by ROA Growth, while Bank Size was included as a control variable. Data were analyzed using Panel Estimated Generalized Least Squares (Panel EGLS) with Cross-section Weights. The findings indicate that ESG Score has a negative but insignificant effect on Sustainable Banking Performance, suggesting that the benefits of ESG implementation are not immediately reflected in short-term profitability. Conversely, Bank Size has a positive and significant effect, indicating that larger banks possess greater capacity to maintain sustainable financial performance. These findings imply that ESG implementation should be viewed as a long-term strategic investment rather than a short-term profitability driver. From the perspective of sustainable and Islamic finance, the findings also suggest that the success of ESG implementation should not be assessed solely by short-term financial outcomes but also by its contribution to ethical governance, stakeholder welfare, and long-term sustainability. This study contributes to the sustainable finance literature by providing recent empirical evidence from the Indonesian banking sector while enriching the discussion of ESG implementation through the perspective of Maqashid Shariah.